Anggaran, Kejelasan Sasaran Anggaran Dan Evaluasi Anggaran Terhadap Kinerja Aparat Pemerintah Daerah Dengan Budaya Kerja Sebagai Pemoderasi: (Studi Pada Pemerintah Provinsi Dki Jakarta) - Rizki Wijaya; Nurmala Ahmar; Harnovinsah (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The objectives of the study are (1) Analyze the effect of participation in budgeting on the performance of local government officials; (2) Analyze the effect of clarity of budget targets on the performance of local government officials; (3) Analyze the effect of budget evaluation on the performance of local government officials; (4) Analyze the work culture moderating the influence between budgeting participation on the performance of dae-rah government officials; (5) Analyze work culture moderating the effect between clarity of budget targets on the performance of local government officials; (6) Analyze work culture moderating the influence between budget evaluation on the performance of local government officials; (7) Analyze the work culture of the performance of local government officials. This study used a quantitative approach. This study used Moderated Regression Analysis (MRA) with smart PLS data processing tools. The results of the study show that (1) Participation in Budgeting does not affect the Performance of Government Officials, (2) Clarity of Budget Targets has a Positive and Significant effect on the Performance of Government Officials, (3) Budget Evaluation has a negative and significant effect on the Performance of Government Officials, (4) Participation in Budgeting moderated by work culture has a positive and significant effect on the Performance of Government Officials, (5) Clarity of Budget Targets moderated by work culture has a negative and significant effect on the performance of government officials, (6) budget evaluation modified by work culture has no effect on the performance of government officials, (7) work culture has a positive and significant effect on the performance of government officials.